Pendidikan Karakter: Al-Qaulu Al-Qadim wa Al-Qaulu Al-Hadits - Arsyad, Azhar (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
This articlediscusses about character building education, Al-Qaulu Al-Qadim Wa al-Qaulu Al-Hadits. Education, accordingly, isaimed to improve the ability of controlling emotion, have tolerant (samahah) and inclusive, that is to invest moral values, such as honesty, loyalty, integrity, trustworthy, respect, responsibility, fairness, and caring. Character building is also intended to make students as cultivating students’ practical skills, creativity, industriousness, cultivating students innovative spirit, self-confidence, andwisdom. Ultimately, all theseelements have been mentioned above will be obtained through character education.